2019
DOI: 10.1051/0004-6361/201834367
|View full text |Cite
|
Sign up to set email alerts
|

Spiral-shaped wavefronts in a sunspot umbra

Abstract: Context. Solar active regions show a wide variety of oscillatory phenomena. The presence of the magnetic field leads to the appearance of several wave modes, whose behavior is determined by the sunspot thermal and magnetic structure. Aims. We aim to study the relation between the umbral and penumbral waves observed at the high photosphere and the magnetic field topology of the sunspot. Methods. Observations of the sunspot in active region NOAA 12662 obtained with the GREGOR telescope (Observatorio del Teide, T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
(57 reference statements)
2
11
0
Order By: Relevance
“…Rouppe van der Voort et al 2003;Nagashima et al 2007). In the figure 10 animation, the evolution of the shocks show spiral patterns (López Ariste et al 2013Su et al 2016;Jess et al 2017;Felipe et al 2019;Kang et al 2019). The radial propagation of the pattern may be apparent propagation rather than physical wave propagation (Bogdan & Judge 2006).…”
Section: Resultsmentioning
confidence: 94%
“…Rouppe van der Voort et al 2003;Nagashima et al 2007). In the figure 10 animation, the evolution of the shocks show spiral patterns (López Ariste et al 2013Su et al 2016;Jess et al 2017;Felipe et al 2019;Kang et al 2019). The radial propagation of the pattern may be apparent propagation rather than physical wave propagation (Bogdan & Judge 2006).…”
Section: Resultsmentioning
confidence: 94%
“…It has been suggested that the single-spiral structure of the wavefronts may be caused by reflections at an umbral light bridge [12], while the multi-spiral structuring may be associated with swirling magnetic fields beneath the umbral photosphere. It has been shown that wavefronts initially move in a counter-clockwise direction in the interior of the umbra, before gradually developing into radial running penumbral waves (RPWs) [13]. The propagation of horizontal waves is related to the direction of magnetic fields, essentially dependent on the magnetic vortex created across the umbral space and with geometric height.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, recent observational works reported that in the horizontal plane, 3 minute oscillations often appear in sunspot umbrae as one-and two-armed spiral wave patterns (SWPs; Sych & Nakariakov 2014;Su et al 2016;Felipe et al 2019). SWPs apparently propagate radially out at the velocity of around 20 km s −1 , and also propagate upward (Su et al 2016).…”
Section: Introductionmentioning
confidence: 99%